Gene–environment interactions in genome‐wide association studies: current approaches and new directions. (28th June 2013) - Winham, Stacey J.; Biernacka, Joanna M.
Abstract : Background: Complex psychiatric traits have long been thought to be the result of a combination of genetic and environmental factors, and gene–environment interactions are thought to play a crucial role in behavioral phenotypes and the susceptibility and progression of psychiatric disorders. Candidate gene studies to investigate hypothesized gene–environment interactions are now fairly common in human genetic research, and with the shift toward genome‐wide association studies, genome‐wide gene–environment interaction studies are beginning to emerge. Methods: We summarize the basic ideas behind gene–environment interaction, and provide an overview of possible study designs and traditional analysis methods in the context of genome‐wide analysis. We then discuss novel approaches beyond the traditional strategy of analyzing the interaction between the environmental factor and each polymorphism individually. Results: Two‐step filtering approaches that reduce the number of polymorphisms tested for interactions can substantially increase the power of genome‐wide gene–environment studies. New analytical methods including data‐mining approaches, and gene‐level and pathway‐level analyses, also have the capacity to improve our understanding of how complex genetic and environmental factors interact to influence psychologic and psychiatric traits. Such methods, however, have not yet been utilized much in behavioral and mental health research. Conclusions: Although methods to investigate gene–environment interactions are available, there is a need for further development and extension of these methods to identify gene–environment interactions in the context of genome‐wide association studies. These novel approaches need to be applied in studies of psychology and psychiatry.